MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN METODE PEMBELAJARAN HOLISTIK MATERI SENI PATUNG KELAS IX-4 SMP NEGERI 29 MEDAN TAHUN PELAJARAN 2019/2020 - T Seri Aminah (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
This shows that students at the time of answering questions are still low. After giving the action during the post-test cycle I, the results obtained from 32 students were 14 students who completed or 43.59%, with a class average of 58.43, there was an increase in learning completeness in the initial test and post-test I of 27.97 %, and in the first cycle the maximum mastery of individual and classical learning outcomes has not been obtained, then proceed to the second cycle and obtained learning mastery, namely from 32 students there are 29 people who have completed learning or 90.62%, and an average of 79, 06, in the second cycle, students have completed to obtain good learning outcomes, so this research ends here.